Torpor: The Rise and Fall of 3-Monoiodothyronamine from Brain to Gut—From Gut to Brain? - Glossmann, Hartmut H.; Lutz, Oliver M. D. (Frontiers in Endocrinology, 2017)
3-Monoiodothyronamine (T1AM), first isolated from rat brain, is reported to be an endogenous, rapidly acting metabolite of thyroxine. One of its numerous effects is the induction of a ”torpor-like” state in experimental animals. A critical analysis of T1AM, to serve as an endogenous cryogen, is given. The proposed biosynthetic pathway for formation of T1AM, which includes deiodinases and ornithine decarboxylase in the upper intestinum, is an unusual one. To reach the brain via systemic circulation, enterohepatic recycling and passage through the liver may occur. The possible role of gut microbiota is discussed. T1AM concentrations in human serum, measured by a specific monoclonal assay are up to three orders of magnitude higher compared to values obtained by MS/MS technology. The difference is explained by the presence of a high affinity binder for T1AM (Apolipoprotein B-100) in serum, which permits the immunoassay to measure the total concentration of the analyte but limits MS/MS technology to detect only the unbound (free) analyte, a view, which is contested here.